Solid-state degradation and visual detection of the nerve agent GB by SA@UiO-66-NH2@PAMAM hydrogel. Issue 44 (24th October 2022) - Shen, Ao; Hao, Xiaohui; Zhang, Lifeng; Du, Man; Li, Mengwen; Zhao, Yongwei; Li, Ziqi; Hou, Lala; Duan, Ruochen; Yang, Yunxu
Abstract : A new sodium alginate (SA) composite hydrogel for rapid solid-state degradation of organophosphorus derivatives and can be used to monitor hydrolysis of nerve agent GB. Abstract : A new sodium alginate (SA) composite hydrogel, SA@UiO-66-NH2 @PAMAM, was synthesized by grafting or immobilizing UiO-66-NH2 and PAMAM to the backbone of SA through covalently binding with glutaraldehyde (GLA) for the rapid solid-state degradation of organophosphorus derivatives without any additional auxiliary substances. SA@UiO-66-NH2 @PAMAM could also be easily processed into cotton fabric to form a recyclable flexible cotton device, SA@UiO-66-NH2 @PAMAM@cotton. Upon introducing the indicator 4-nitro-(dimethyl- tert -butyl) silica ether ( P -NSE) to the composite hydrogel system to form a new Gel-1, degradation changes could be measured by using the product of nitrophenol (P-NP) with a yellow color in the gel to monitor the hydrolysis of the nerve agent GB. Therefore, the integrative multifunctional hydrogel Gel-1@cotton with a smartphone as a portable platform was used to realize the real-time monitoring of changes of GB degradation under visible light.